CERTIFICATE OF ACCREDITATION BACHELOR OF SOCIAL SCIENCES IN INDUSTRIAL RELATIONS AND EMPLOYMENT WITH HONOURS (MQA/FA10754) (2018) - Jasmine, Jugah
MALAYSIAN QUALIFICATION AGENCY- BACHELOR OF SOCIAL SCIENCES IN INDUSTRIAL RELATIONS AND EMPLOYMENT WITH HONOURS (MQA/FA10754) (2018)- FACULTY OF SOCIAL SCIENCES AND HUMANITIES